Application of mid‐infrared free‐electron laser tuned to amide bands for dissociation of aggregate structure of protein. (1st January 2016) - Kawasaki, Takayasu; Yaji, Toyonari; Ohta, Toshiaki; Tsukiyama, Koichi
Abstract : A mid‐infrared free‐electron laser (FEL) is a linearly polarized, high‐peak powered pulse laser with tunable wavelength within the mid‐infrared absorption region. It was recently found that pathogenic amyloid fibrils could be partially dissociated to the monomer form by the irradiation of the FEL targeting the amide I band (C=O stretching vibration), amide II band (N—H bending vibration) and amide III band (C—N stretching vibration). In this study, the irradiation effect of the FEL on keratin aggregate was tested as another model to demonstrate an applicability of the FEL for dissociation of protein aggregates. Synchrotron radiation infrared microscopy analysis showed that the α‐helix content in the aggregate structure decreased to almost the same level as that in the monomer state after FEL irradiation tuned to 6.06 µm (amide I band). Both irradiations at 6.51 µm (amide II band) and 8.06 µm (amide III band) also decreased the content of the aggregate but to a lesser extent than for the irradiation at the amide I band. On the contrary, the irradiation tuned to 5.6 µm (non‐absorbance region) changed little the secondary structure of the aggregate. Scanning‐electron microscopy observation at the submicrometer order showed that the angular solid of the aggregate was converted to non‐ordered fragments by the irradiation at each amide band, while the aggregate was hardly deformed by the irradiation at 5.6 µm. These results demonstrate that the amide‐specific irradiation by the FEL was effective for dissociation of the protein aggregate to the monomer form.